Evolution and slow decay of an unusual narrow ring of relativistic electrons near L ~ 3.2 following the September 2012 magnetic storm. Issue 14 (26th July 2013) - Thorne, R. M.; Li, W.; Ni, B.; Ma, Q.; Bortnik, J.; Baker, D. N.; Spence, H. E.; Reeves, G. D.; Henderson, M. G.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; et al.
Abstract: [1] A quantitative analysis is performed on the decay of an unusual ring of relativistic electrons between 3 and 3.5 RE, which was observed by the Relativistic Electron Proton Telescope instrument on the Van Allen probes. The ring formed on 3 September 2012 during the main phase of a magnetic storm due to the partial depletion of the outer radiation belt for L > 3.5, and this remnant belt of relativistic electrons persisted at energies above 2 MeV, exhibiting only slow decay, until it was finally destroyed during another magnetic storm on 1 October. This long‐term stability of the relativistic electron ring was associated with the rapid outward migration and maintenance of the plasmapause to distances greater than L = 4. The remnant ring was thus immune from the dynamic process, which caused rapid rebuilding of the outer radiation belt at L > 4, and was only subject to slow decay due to pitch angle scattering by plasmaspheric hiss on timescales exceeding 10–20 days for electron energies above 3 MeV. At lower energies, the decay is much more rapid, consistent with the absence of a long‐duration electron ring at energies below 2 MeV. Key Points: Relativistic electrons injected into the plasmasphere have long lifetimes The loss rate is controlled by scattering by whistler‐mode hiss Isolated rings of relativistic electrons form during magnetic storms